1985
DOI: 10.1002/pen.760250111
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of particle size distribution in continuous emulsion polymerization styrene monomer

Abstract: A detailed mathematical model for absolute particle‐size distribution in continuous emulsion polymerization of styrene monomer is proposed on the basis of the modified population‐balance theory. The computer simulation is then performed for styrene polymerization as an example of a nondesorption system. The effects of emulsifier and initiator concentrations as well as mean residence time on the absolute particle‐size‐distribution function, total concentration of polymer particles, conversion, average number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hence, these two particle nucleation processes can be classified into two regimes as regime‐I (below CMC) and regime‐II (above CMC). Thorough investigations of various aspects of colloidal particles synthesis by emulsion polymerization in both the regime have been carried out both theoretically and experimentally 23–29. However, studies on the crosslinked charged copolymer particles are not reported extensively in the literature 7, 13–16, 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these two particle nucleation processes can be classified into two regimes as regime‐I (below CMC) and regime‐II (above CMC). Thorough investigations of various aspects of colloidal particles synthesis by emulsion polymerization in both the regime have been carried out both theoretically and experimentally 23–29. However, studies on the crosslinked charged copolymer particles are not reported extensively in the literature 7, 13–16, 30–32.…”
Section: Introductionmentioning
confidence: 99%